Sur les sociétés précapitalistes - Marx, Karl; Centre d'Etudes et de Recherches Marxistes; Lenin, Vladimir Iljitsj; Engels, Friedrich; Godelier, Maurice (Paris : Editions Sociales, 1970)
Bibliotheek François Vercammen
Frans
Monografie